1976
DOI: 10.1037/0022-006x.44.6.898
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of return to a psychiatric hospital.

Abstract: Social factors as measured by a community adjustment scale and other known variables associated with recidivism were examined for their ability to predict rchospitalization of former menial patients. Multiple linear regression analyses indicated that two of the subscales of the Self-Assessment Guide, the number of previous hospital admissions, and whether the individual had been in the hospital 1 year prior to admission accounted for a sizable portion of variance. These results suggest that social factors are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…The role that gender plays in recidivism is unresolved as one study found higher rates for females (Setze & Bond, 1985) while five studies found males were more likely to be re-hospitalized (McCrainie & Mizzell, 1978;Miller & Willer, 1976;Sylvester & Bean, 1989). However, 14 studies found no relationship between gender and recidivism (Masaki et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The role that gender plays in recidivism is unresolved as one study found higher rates for females (Setze & Bond, 1985) while five studies found males were more likely to be re-hospitalized (McCrainie & Mizzell, 1978;Miller & Willer, 1976;Sylvester & Bean, 1989). However, 14 studies found no relationship between gender and recidivism (Masaki et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, we could not randomize and could not match. However, in a previous study (Miller and Willer, 1976) we did run the relevant regression equation with respect to recidivism, prior to development of the experimental program, and found little or no effect due to differences in the unit of treatment. Table 1.…”
Section: Resultsmentioning
confidence: 86%
“…Anthony ( I 980) has argued for the use of posthospital employment as a criterion that measures both the client's well-being and the benefit to the tax-paying public. One six-month follow-up study showed nonrecidivists to be characterized by higher self-ratings on such job-relevant factors as ability to handle money, source of financial support, work behavior, job-seeking behavior, and ability to deal effectively with anger (Miller & Miller, 1976). From a social network perspective, employment indicates a community tie of significant value.…”
Section: Social Ties In Community Adjustmentmentioning
confidence: 99%